2013
DOI: 10.1007/978-3-319-00699-4_3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Soil Information in Land Degradation and Desertification Mapping: A Review

Abstract: Mapping land degradation and desertification (LDD) has generally been considered as a complex task, and past efforts have produced contrasting results. Until recently, this exercise has often been seen as a soil scientist's task by the international community. However, the actual role and ''weight'' of soil information in LDD mapping at different spatial scales has been influenced and constrained by the changing conceptual frameworks and data availability. This chapter reviews these aspects and discusses the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The demand for food is putting greater pressures on the natural resource base [58]. Assessments of land degradation in the region vary in methodology and by type of degradation being experienced [30,52,61]. The GLASOD survey, based on expert opinion, concluded that in the early 1980s about 16.7% of SSA experienced serious humaninduced land degradation [35,60].…”
Section: The Extent Of Land Degradation In Eastern Africamentioning
confidence: 99%
See 1 more Smart Citation
“…The demand for food is putting greater pressures on the natural resource base [58]. Assessments of land degradation in the region vary in methodology and by type of degradation being experienced [30,52,61]. The GLASOD survey, based on expert opinion, concluded that in the early 1980s about 16.7% of SSA experienced serious humaninduced land degradation [35,60].…”
Section: The Extent Of Land Degradation In Eastern Africamentioning
confidence: 99%
“…More recently, the Economics of Land Degradation (ELD) initiative defines land degradation as 'reduction in the economic value of ecosystem services and goods derived from land' (ELD 2013). Assessments of land degradation vary in methodology and outcome [30,52,61]. There are two broad approaches to evaluate land degradation: ground-based measurements and remote sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Soil is essentially a non-renewable resource with potentially rapid degradation rates and extremely slow formation and regeneration processes (Zucca et al, 2014). The integration between Geographic information system and modeling plays a key role in quantitative studies of soil properties and land evaluation for different land uses.…”
Section: Introductionmentioning
confidence: 99%
“…The complex interaction of all these factors may lead to a number of negative effects, including the damaging of ecosystems, biodiversity loss (Biggs et al, 2008), declining productivity and agricultural yields (El Baroudy & Moghanm, 2014, Sonneveld et al, 2015 or the complete loss of cropland, land use conflicts and outmigration. Degraded land may also no longer provide a range of ecosystem functions and services (Salami & Adepoju, 2012;Hochstrasser et al, 2014;Zucca et al, 2014). The described processes in turn directly and indirectly affect many sectors such as environment, agriculture, water resources, energy, pests/diseases and require appropriate adaptation measures.…”
Section: Introductionmentioning
confidence: 99%
“…One of the central questions in land degradation assessments is which regions are likely to be hit hardest (Bai et al, 2008). In several publications (Puigdefábregas & Mendizábal, 2004;Garcìa et al, 2009;Payet et al, 2013;Favretto et al, 2014;Zucca et al, 2014;Vågen et al, 2015) the need for adequate mapping and operational methods to identify land degradation hot-spots has been expressed. A link of degradation assessments to climate information is also in high demand (Sivakumar & Stefanski, 2007).…”
Section: Introductionmentioning
confidence: 99%